PENERAPAN APLIKASI SP4N-LAPOR DALAM MANAJEMEN PENGADUAN MASYARAKAT DI KOTA SOLOK - Lurensia Nindyta Angelina Haspo; Aldri Frinaldi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
This aims this study is to determine the Application of SP4N-LAPOR! In Solok city. SP4N-LAPOR! is an online application that is useful to make it easier for the public to submit complaints and for the government to find out the problems of public services in Solok city so that it is faster to be fixed. This research is a qualitative research which using descriptive methods. Informants were selected using a purposive sampling technique. In collecting data the research instruments were: form of interviews, observation and documentation studies. Data validity testing techniques was using the triangulation method. While the data analysis technique is done by reducing data, displaying data, and drawing conclusions and studies that have been determined. The results of the study showed the Implementation of SPAN-LAPOR aplication in public complain management in Solok city was not running well yet.